2013
DOI: 10.2527/jas.2012-6197
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for different measures of feed efficiency and related traits in boars of three pig breeds1

Abstract: Residual feed intake (RFI) is commonly used as a measure of feed efficiency at a given level of production. A total of 16,872 pigs with their pedigree traced back as far as possible was used to estimate genetic parameters for RFI, growth performance, food conversion ratio (FCR), body conformation, and feeding behavior traits in 3 Danish breeds [Duroc (DD), Landrace (LL), and Yorkshire (YY)]. Two measures of RFI were considered: residual feed intake 1 (RFI1) was calculated based on regression of daily feed inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

43
127
10
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(184 citation statements)
references
References 37 publications
43
127
10
4
Order By: Relevance
“…Given these differing emphases on selection, it is reasonable that the genetic architeture of these two breeds differs with respect to traits like feed efficiency that are targetted more intesively for selection within Durocs. In accordance with this, we have found that the genetic variation (heritability) of RFI is higher in Yorkshire compared to Duroc pigs (Do et al, 2013a). Therefore, while the biological mechanisms are likely conserved even across species (Mayr, 1963; Raff, 1996), the genetic regulation of these mechanisms is not necessarily conserved, and investigating the genetics underlying the same phenotype in a different breed could provide novel insights into the biological mechanisms underlying feed efficiency.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Given these differing emphases on selection, it is reasonable that the genetic architeture of these two breeds differs with respect to traits like feed efficiency that are targetted more intesively for selection within Durocs. In accordance with this, we have found that the genetic variation (heritability) of RFI is higher in Yorkshire compared to Duroc pigs (Do et al, 2013a). Therefore, while the biological mechanisms are likely conserved even across species (Mayr, 1963; Raff, 1996), the genetic regulation of these mechanisms is not necessarily conserved, and investigating the genetics underlying the same phenotype in a different breed could provide novel insights into the biological mechanisms underlying feed efficiency.…”
Section: Introductionsupporting
confidence: 85%
“…A total of 596 Yorkshire pigs had both phenotypic (RFI) and genotypic records (based on PorcineSNP60 Illumina iSelect BeadChip). The method of calculation of RFI has been previously discussed in detail (Do et al, 2013a). In summary, RFI was computed as the difference between the observed average daily feed intake and the predicted daily feed intake using two statistical models.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, improving feed efficiency (FE) is an important approach for reducing pig production expenses. Currently, two highly correlated indicators, namely, residual feed intake (RFI) and feed conversion ratio (FCR), are being used to measure the FE trait123. Low levels of FCR/RFI indicate high FE4.…”
mentioning
confidence: 99%
“…Thus far, two highly correlated indicators, i.e. , feed conversion ratio (FCR) and residual feed intake (RFI), are used to measure FE, and a low FCR/RFI level denotes an improvement in FE (Do et al 2013). Microarray analysis has revealed that lipogenesis and steroidogenesis in liver tissues are related to the FE of pigs (Lkhagvadorj et al 2010).…”
mentioning
confidence: 99%